Yahoo Web Search

  1. Sort by

  1. If A, B and N are given, why don't you give them to me so I can work with them!?!?!? I = (N-K+A)/N J = (N-L+B)/N

    1 Answers · Science & Mathematics · 05/09/2012

  2. ...i) = 1 * (2^(n - j + 1) - 1) / (2 - 1) = 2^(n - j + 1) - 1 Therefore: a_n = ∑ (j = 1 to n) ∑ (i = j to n) 2^(n - i) = ∑ (j = 1 to n) [2^(n - j + 1) - 1] = ∑ (j...

    1 Answers · Science & Mathematics · 30/06/2013

  3. ...from N. Then, if i > j, then n(i) > n(j), and so a(n(i)) >= a(n(j)). Thus, a(n(m)) is monotone increasing. Decreasing...

    1 Answers · Science & Mathematics · 04/02/2012

  4. ...a_(1, j) * x_j , Σ(j=1 to n) a_(2, j) * x_j , ..., Σ(j=1 to n) a_(n, j) * x_j) Therefore, f(x) = x₁ Σ(j=1 to n) a_(1, j) * x...

    1 Answers · Science & Mathematics · 12/10/2011

  5. ... the n-th root of the product of all n of them: GM(a[1], ..., a[n]) = (∏[j=1,n] a[j])^(1/n) For n = 2, this is GM(a, b) = √(ab...

    3 Answers · Science & Mathematics · 15/04/2011

  6. ...matrix. That is, for any j: a(1, j)b(1, j) + a(2, j)b(2, j) + ... + a(n, j)b(n, j) = 0 But then, all the action happens in the jth column, where...

    1 Answers · Science & Mathematics · 11/03/2014

  7. ...the Binomial Theorem: (a + b)^n = sum(j=0 to n) nCj * a^(n - j) * b^j. If we let a = 1 and b = 3 (a should be 1 to eliminate the n - j exponent...

    2 Answers · Science & Mathematics · 07/08/2010

  8. I'm not very sure, but if none of the other answers on here work, seach on google... "letter equation" or "variable equation" and see what comes up.

    3 Answers · Science & Mathematics · 28/09/2009

  9. ... terms of the binomial expansion of (a + b)^n are C(n,j) * a^(n - j) * b^j Since we want the term for t^8 then n - j = 8. Given n...

    3 Answers · Science & Mathematics · 18/08/2009

  10. Well in this case the formula would be (n C n-j)*a^(n-j)*(x^2)^j x^8 = (x^2)^4 so j = 4 n = 7 n - j = 3 a = 3 So the...

    2 Answers · Science & Mathematics · 26/07/2009

  1. Try asking your question on Yahoo Answers